Strategi pembelajaran bahasa melayu mengikut jantina di luar kelas - Zamri Mahamod; Mohamed Amin Embi (penerbit ukm, 2005)
This article describes findings of a descriptive case study designed to examine the range of language learning strategies employed by male and female students for learning of the Malay language out of the classroom based on the major language skills (listening, speaking, reading and writing). Data was collected using an in-depth interview. Eight Form 4 students were purposively selected as respondents for the study consisting of four good language learners and four poor language learners representing both gender. The respondents were required to elicit language learning strategies that they usually employ to learn the Malay language out of the classroom for improving their listening, speaking,reading and writing skills. The interview data was analyzed, categorized and coded for recurrent themes. For realibility of the categories indentified, the Cohen Kappa Index Analysis was used. Results of the study indicate that participants employed a wide range of language learning strategies for learning the Malay language out of the classroom. The good learners however reported using a wider range of language learning strategies in comparison to the poor learners especially in terms of language activities and utilizing the information technology. Male students also reported employing a wider range of language leaning strategies in comparison to female students in the listening, speaking and writing skills.